2015
DOI: 10.1371/journal.pone.0131246
|View full text |Cite
|
Sign up to set email alerts
|

Cold Regime Interannual Variability of Primary and Secondary Producer Community Composition in the Southeastern Bering Sea

Abstract: Variability of hydrographic conditions and primary and secondary productivity between cold and warm climatic regimes in the Bering Sea has been the subject of much study in recent years, while interannual variability within a single regime and across multiple trophic levels has been less well-documented. Measurements from an instrumented mooring on the southeastern shelf of the Bering Sea were analyzed for the spring-to-summer transitions within the cold regime years of 2009–2012 to investigate the interannual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 46 publications
(70 reference statements)
1
14
0
Order By: Relevance
“…The mechanism that has been proposed to explain these observed patterns focuses on the atmosphere‐ice‐ocean dynamics that influence water temperature and phytoplankton production (Napp, Kendall, & Schumacher, ; Sigler et al., ). Cold years on the southeastern Bering Sea shelf have significant winter sea‐ice extent, colder water temperatures, and an ice‐associated spring algal bloom (Hunt et al., ; Sigler, Stabeno, Eisner, Napp, & Mueter, ; Stabeno, Bond, Kachel, Salo, & Schumacher, ; Stabeno, Schumacher, Davis, & Napp, ), although considerable variability within cold years is observed (Stauffer, Miksis‐Olds, & Goes, ). Warm years are ice‐free, have warmer water temperatures, and an open‐water spring bloom as the water column stratifies (Hunt et al., ; Sambroto et al.,; Sigler et al., ; Stabeno et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism that has been proposed to explain these observed patterns focuses on the atmosphere‐ice‐ocean dynamics that influence water temperature and phytoplankton production (Napp, Kendall, & Schumacher, ; Sigler et al., ). Cold years on the southeastern Bering Sea shelf have significant winter sea‐ice extent, colder water temperatures, and an ice‐associated spring algal bloom (Hunt et al., ; Sigler, Stabeno, Eisner, Napp, & Mueter, ; Stabeno, Bond, Kachel, Salo, & Schumacher, ; Stabeno, Schumacher, Davis, & Napp, ), although considerable variability within cold years is observed (Stauffer, Miksis‐Olds, & Goes, ). Warm years are ice‐free, have warmer water temperatures, and an open‐water spring bloom as the water column stratifies (Hunt et al., ; Sambroto et al.,; Sigler et al., ; Stabeno et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Warm years are ice‐free, have warmer water temperatures, and an open‐water spring bloom as the water column stratifies (Hunt et al., ; Sambroto et al.,; Sigler et al., ; Stabeno et al., ). The combined effects of primary production and temperature have been hypothesized to drive the observed differences in the zooplankton community (Banas et al., ; Coyle et al., ; Hunt et al., ; Sigler et al., ; Stauffer et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…() study concluded with records from 2012 when a cold climatic regime in the Bering Sea, which started in 2009, shifted to a warm climatic regime (Stauffer et al . ). These four cold climate years from 2009 to 2012, and particularly 2012, saw more expansive and thicker ice that retreated later in the season, stratifying the water column earlier and more tightly coupling the biomass of primary production with hydrographic conditions (Stauffer et al .…”
Section: Available Data: a Timeline Of Pals Deployed At Four Sites Inmentioning
confidence: 97%
“…These four cold climate years from 2009 to 2012, and particularly 2012, saw more expansive and thicker ice that retreated later in the season, stratifying the water column earlier and more tightly coupling the biomass of primary production with hydrographic conditions (Stauffer et al . ). During cold climate years, the Oscillating Control Hypothesis (OCH) states that fisheries are controlled by bottom‐up mechanisms and biomass is transported to benthic communities instead of pelagic fishery populations (Hunt et al .…”
Section: Available Data: a Timeline Of Pals Deployed At Four Sites Inmentioning
confidence: 97%